Conceptualizações de vida e de morte em notas de suicídio escritas por brasileiros no século XXI - Knoth, João Vitor (2024)
The research undertaken aimed to study, using the theoretical-methodological framework of Cognitive Linguistics, the phenomenon of conceptualization of life and death in a specific corpus, dated and located, of great socioemotional impact: suicide notes. Drawing on the assumptions of Lakoff and Johnson (2002 [1980]), who define metaphor as an important link between cognition and language, the study conducted a qualitative analysis of the concepts of life and death in suicide notes, considering that, in this corpus, there is great exposure regarding these concepts due to the entire context surrounding their production. The metaphors and metonymies found by the research are categorized and analyzed to elucidate important linguistic aspects for suicide studies and also to provide a solid foundation for possible future comparative research. The corpus collection for this dissertation followed the parameters presented by Mattos and Silva (2008), in line with the broad nature of the research. In this work, the term "note" is understood in its broadest sense, anchored in the assumptions of Barbosa (2012) for the constitution of historical corpora from the notion of Discursive Tradition, encompassing these possible genres based on their production purpose. The notes derive from virtual reports that covered suicide cases and published texts left by the victims; these could be materialized in various genres, such as: social media posts, notes, letters, and notes themselves. It was observed, from the results obtained from the categorization and analysis of metaphors and metonymies, that some were more prominent than others. The metaphors LIFE IS A JOURNEY and LIFE IS A WAR appeared in the notes with quite prominence, being mainly linked to a religious/Christian bias. The activation of the EFFORT frame was recurrently observed from different schematic metaphors. For the conceptualization of DEATH, a mirroring of LIFE metaphors was observed. Religious belief and socioeconomic variables were the most significant elements in the meaning of the concepts. These results may indicate a possible aspect of semantic variation within the analyzed corpus, which could contribute to a possible mapping of the verbal character of suicidal behavior; the analysis of conceptualizations constitutes an important interdisciplinary study material for a better understanding of the problem of suicide.